Adolescent girls" voices on their need for sexuality education: A cry for mutual sexual emancipation - Koch, Ronél (HTS teologiese studies, 2019)
‘Teachers expect parents to teach you. Parents expect teachers to teach you. So actually you learn nothing and nobody wants to talk about it’. This quote from this research study is an adolescent girls’ cry for liberation from the silence related to sexuality because of the general reluctance of adults to talk to them about it. Given the growing concerns raised about the sexual and reproductive health of adolescents in South Africa, the aim of this study was to conduct research with adolescent girls as subjects in order for girls’ voices to enhance adult researchers’ understanding of children’s need for support and guidance in the context of sexuality education. The purposively selected sample included 75 participants from three diverse high schools in the Western Cape. The research was conducted using a phenomenological approach that values the lived experiences of participants as significant in contributing to the knowledge on adolescent sexuality. A qualitative interpretative research design was applied to collect the data. This article argues that adults cannot help adolescents in their sexual emancipation – to be free – if they themselves are not free. If they were free, they would have been able and willing to engage with adolescents in every aspect, which includes their sexuality. Including adolescent girls as partners in transforming sexuality education is presented as a core principle for the sexual emancipation of both adolescent girls and adults.